2011
DOI: 10.1038/jhh.2011.78
|View full text |Cite
|
Sign up to set email alerts
|

Relation of central and brachial blood pressure to left ventricular hypertrophy. The Czech Post-MONICA Study

Abstract: Central blood pressure (BP) has been shown to be a better predictor of target organ damage and cardiovascular events than brachial BP. Whether central BP is a better predictor of left ventricular hypertrophy (LVH) determined by electrocardiography (ECG) is not known. Radial applanation tonometry and ECG were performed in 728 subjects from the Czech Post-MONICA Study (a randomly selected 1% population sample). LVH was determined using the Sokolow-Lyon index and Cornell product; central pressure was derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 23 publications
0
21
0
5
Order By: Relevance
“…Whereas the relation between peripheral blood pressure and cardiac structure has been well documented, few studies have assessed relations among cardiac structure, central hemodynamics, and vascular stiffness using detailed tonometry measures. These prior studies were limited by small sample size or an indirect assessment of central hemodynamics, restricted to non‐European ancestry individuals or relied on electrocardiographic LV hypertrophy . In a sample of 1272 Chinese indiviudals, Wang et al reported that central pulse pressure was associated with LV mass .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the relation between peripheral blood pressure and cardiac structure has been well documented, few studies have assessed relations among cardiac structure, central hemodynamics, and vascular stiffness using detailed tonometry measures. These prior studies were limited by small sample size or an indirect assessment of central hemodynamics, restricted to non‐European ancestry individuals or relied on electrocardiographic LV hypertrophy . In a sample of 1272 Chinese indiviudals, Wang et al reported that central pulse pressure was associated with LV mass .…”
Section: Discussionmentioning
confidence: 99%
“…24 In the Czech Post-MONICA Study, the presence of LVH was assessed by ECG using either Sokolow-Lyon or Cornell voltage criteria rather than echocardiography. 25 Among 657 participants who had both ECG and radial applanation tonometry, the presence of ECG-LVH was not related to any BP variable in those <45 years of age. Among older participants, the odds ratios to predict the presence of ECG-LVH were higher for central SBP and PP than those for brachial pressures.…”
Section: Hypertrophymentioning
confidence: 89%
“…17,18 Some authors have identified that central pressure, compared with brachial pressure, correlates better with intermediate cardiovascular risk markers such as carotid intima-media thickness and left ventricular hypertrophy. 19,20 Several studies have reported an independent relationship between central pressure and future cardiovascular events, including in elderly patients with coronary disease and chronic kidney disease. 14,21-23 However, other studies have not found a superior predictive value for central pressure over brachial pressure.…”
Section: Measures Of Central and Peripheral Pressures: Differences Anmentioning
confidence: 99%